Towards a pedagogy of accessibility: The need for critical learning spaces in media accessibility education and training - Greco, Gian Maria (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2020)
Until now, the debate on education and training in accessibility has largely ignored the core competences of the accessibility expert, as it has tended to focus exclusively on context- and field-related skills. Looking at the case of media accessibility through the critical lens of accessibility studies, the article calls for the development of a theoretical reflection on education and training. Such reflection could then solidly support extensive investigation of the specific skills of accessibility researchers, professionals and policy-makers, frame analyses of current programmes, and strengthen proposals for new curricula and professional profiles. The article contributes to such a reflection by advancing and discussing the inclusion of critical learning spaces within vocation- and research-oriented courses. Using the critical lens of accessibility studies, the article also investigates whether education and training in audiovisual translation and media accessibility have been mostly dominated by some discriminatory normative frameworks, such as the medical model of disability, and how this is influenced by and in turn influences practices. The article suggests that this problem requires a (re)design of education (and practices) using the tools that constitute the critical apparatus of accessibility studies, such as the human variation paradigm, the social model of accessibility, the universalist account of access, the poietic model of agency, and proactive and user-centred approaches. Ultimately, the article outlines the very first traits of a pedagogy of accessibility, that is, a systematic approach to the practice(s) of teaching and learning accessibility.